Les paysages pré- et post-apocalyptiques de J.D. Kurtness - Voldřichová Beránková, Eva (Ponti/Ponts, 2024)
Julie D. Kurtness is a young Quebec writer of Innu origin who has distinguished herself by the strange dystopian universes that she depicts in her science fiction novels and short stories. The article examines the nature of Kurtnessian pre- and post-apocalyptic landscapes in order, on the one hand, to distinguish them from contemporary commercial production (especially Hollywood) as well as from the traditional Christian imaginary and, on the other, to compare them to newly emerging « post-Anthropocene » aesthetics.